Playing with religion in digital games - Campbell, Heidi, 1970-; Grieve, Gregory P. (Gregory Price), 1964- (Digital game studies., 2014)
Shaman, paragon, God-mode: modern video games are heavily coded with religious undertones. From the Shinto-inspired Japanese video game Okami to the internationally popular The Legend of Zelda and Halo, many video games rely on religious themes and symbols to drive the narrative and frame the storyline. Playing with Religion in Digital Games explores the increasingly complex relationship between gaming and global religious practices. For example, how does religion help organize the communities in MMORPGs such as World of Warcraft? What role has censorship played in localizing games like Actraiser in the western world? How do evangelical Christians react to violence, gore, and sexuality in some of the most popular games such as Mass Effect or Grand Theft Auto? With contributions by scholars and gamers from all over the world, this collection offers aunique perspective to the intersections of religion and the virtual world.